Generating high-resolution total canopy SIF emission from TROPOMI data: Algorithm and application - Zhang, Zhaoying; Zhang, Yao; Zhang, Yongguang (Remote sensing of environment, 2023)
Solar-induced chlorophyll fluorescence (SIF) is a rapidly advancing front in modeling global terrestrial gross primary production (GPP). Canopy total SIF emissions (SIFtotal) are mechanistically linked to the plant photosynthesis, and can be estimated from satellite observed SIF (SIFobs) through radiative transfer modeling. However, the current satellite SIFobs and thus SIFtotal are available only at coarse spatial resolutions from several kilometers to tens of kilometers, inhibiting the application at fine spatial scales. Here, we proposed an algorithm to generate both global high-resolution SIFtotal (HSIFtotal) and high-resolution SIFobs (HSIFobs) at 1 km from low-resolution SIFobs (LSIFobs) from the TROPOspheric Monitoring Instrument (TROPOMI), which has a spatial resolution at nadir of 3.5 km by 5.6–7 km. Our statistical method is based on the law of energy conservation and uses satellite derived fraction of absorbed photosynthetically active radiation, fluorescence efficiency, and the escape probability of fluorescence. We evaluated the accuracy of our HSIFtotal using the Orbiting Carbon Observatory-2 SIF (R2 = 0.78). We found that the spatial resolution had clear effects on the relationship between HSIFtotal and GPP. We also compared HSIFtotal to 8-day averaged tower GPP from 135 flux sites and found that they were better correlated when HSIFtotal was averaged over a 1-km radius around the tower than when averaged over a larger radius. Our study provided a unique high-resolution HSIFtotal product, which will advance the estimation of GPP by extrapolating site-level relationships to the global scale. •We generated global high resolution total canopy fluorescence emission (SIFtotal).•HSIFtotal is evaluated using the Orbiting Carbon Observatory-2 SIFtotal.•The relationship between HSIFtotal and GPP is more consistent across sites.•HSIFtotal is better related to gross primary production (GPP) than SIFobs.